A new interpretation of the √7×√7 R19.1° structure for P adsorbed on a Ni(111) surface. Issue 1 (31st December 2019) - Barrow, Elizabeth; Seuser, Grant S.; Ariga-Miwa, Hiroko; Chen, Donna A.; Lauterbach, Jochen; Asakura, Kiyotaka
ABSTRACT: We have studied P adsorption on Ni(111), a system which shows complex adsorbate structures. We determined the phase diagram of the surface P adsorbed on Ni(111). At low coverage, amorphous P was observed. At temperatures between 373 and 673 K and coverages above 0.1 monolayer, we found a 7 × 7 R 19.1 ∘ structure, but above 673 K, other complex structures were created. These structures seemed to correlate with each other and we reinterpret a 7 × 7 R 19.1 ∘ structure of P adsorbed on Ni(111) based on the similarities of these surface structures. The new rectangular structure for the 7 × 7 19.1 ∘ is discussed in relation to the Ni2 P local structure. Graphical abstract: uf0001